A test of the investment model among asexual individuals: The moderating role of attachment orientation - Brozowski, Alexandra; Connor-Kuntz, Hayden; Lewis, Sanaye; Sinha, Sania; Oh, Jeewon; Weidmann, Rebekka; Weaver, Jonathan R.; Chopik, William J. (Frontiers in Psychology, 2022)
Many asexual individuals are in long-term satisfying romantic relationships. However, the contributors to relational well-being among asexual individuals have received little attention. How do investment model characteristics and attachment orientations predict relationship commitment among asexual individuals? Our study looked at a sample of 485 self-identified asexual individuals currently in a romantic relationship (Mage = 25.61, SD = 6.24; MRelationshipLength = 4.42 years, SD = 4.74). Individuals reported on Investment Model characteristics (i.e., their relationship satisfaction, investment, alternatives, commitment) and their attachment orientations. Satisfaction, investment, and fewer alternatives were associated with greater commitment. Attachment orientations only occasionally moderated the results: for people low in anxiety, satisfaction and investment were more strongly related to commitment compared to people high in anxiety. The current study provided an extension of the Investment Model to describe romantic relationships among asexual individuals.